2014
DOI: 10.5851/kosfa.2014.34.5.597
|View full text |Cite
|
Sign up to set email alerts
|

Quality Evaluation of Pork with Various Freezing and Thawing Methods

Abstract: In this study, the physicochemical and sensory quality characteristics due to the influence of various thawing methods on electro-magnetic and air blast frozen pork were examined. The packaged pork samples, which were frozen by air blast freezing at −45℃ or electro-magnetic freezing at −55℃, were thawed using 4 different methods: refrigeration (4±1℃), room temperature (RT, 25℃), cold water (15℃), and microwave (2450 MHz). Analyses were carried out to determine the drip and cooking loss, water holding capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
(24 reference statements)
1
11
0
Order By: Relevance
“…The cooking loss of the meat was determined for the three muscles types (thigh, drumstick and breast) as described by (Ku et al, 2014) with minor modifications. The samples were weighed and heated at 75°C in a water bath for 25minutes, and each cooked sample was cooled to room temperature, blotted dry and weighed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooking loss of the meat was determined for the three muscles types (thigh, drumstick and breast) as described by (Ku et al, 2014) with minor modifications. The samples were weighed and heated at 75°C in a water bath for 25minutes, and each cooked sample was cooled to room temperature, blotted dry and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…Cooking loss (%) = {(weight before cook − weight after cook)/ weight before cook} × 100 Likewise, the thawing loss for the three muscles types (thigh, drumstick and breast) were determined by thawing the samples at room temperature for 3 hours as described by (Ku et al, 2014) with minor modifications. The difference between the initial weight and the final weights was used in calculating the thaw loss as:…”
Section: Methodsmentioning
confidence: 99%
“…In these samples, microscopic observations showed large spaces within the muscle fibers, whereas these spaces in the magnetically frozen samples were small and scattered throughout the muscle fibers. Kim and others (,b), Ku and others (), and Choi and others () reported reduced total freezing times and improved quality attributes in beef, pork, and chicken samples frozen in a magnetic freezer (ABI Co., Ltd.) at –55 °C compared with samples frozen in an air blast freezer at –45 °C. However, as freezer temperatures were not the same, it is not possible to deduce whether the improvements detected were produced by the MF or by the lower temperature applied.…”
Section: Experimental Data About the Effects Of Mfs On Freezingmentioning
confidence: 97%
“…The user can program different “CAS conditions” (0% to 100% CAS) at the control panel, but the MF intensities and frequencies associated to these “CAS conditions” are not specified. Measurements with devices not usually employed in freezing research (teslameters and oscilloscopes, for example) are needed to correctly describe commercial equipment and, for this reason, many authors do not report these data (Kim and others ,b; Ku and others ; Choi and others ). Therefore, the experimental conditions of assays published in the literature must be analyzed carefully and the results should be treated with caution before drawing conclusions.…”
Section: Experimental Data About the Effects Of Mfs On Freezingmentioning
confidence: 99%
“…Even though the freezing rates achieved in each device were very different, the authors only found minor differences among the samples. By contrast, Kim et al (2013a), Kim et al (2013b), Ku et al (2014), and Choi et al (2015) froze beef, pork, and chicken samples in both a CAS freezer at −55 °C and an air-blast freezer at −45 °C. They concluded that electromagnetic freezing reduced the total freezing times and preserved the quality attributes of the samples better than air-blast freezing.…”
Section: Introductionmentioning
confidence: 93%